2022
DOI: 10.1590/2326-4594-jiems-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Current Scenario and Future Direction of Newborn Screening and Management Program for Phenylketonuria in Bangladesh

Abstract: Phenylketonuria (PKU) is a correctable inborn error of metabolism which causes lethal intellectual delay and neurobehavioral anomalies. A screening package, especially for early recognition can support to regulate the PKU process of most patients. Newborn screening program in any country focuses at the earliest detection of inheritance deficiency disorders in order to avoid the most severe repercussion by appropriate medication. This screening program needs a concomitant diagnosis and involves additional clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The pathogenic variant c 60 + 5G > T was found in 26 patients, and brain damage was observed in two patients homozygous for this variant. This study observed that the general genotype/phenotype concordance was 83.8% when compared with identical genotypes reported in the BIOPKUdb [ 20 ].…”
Section: Reviewmentioning
confidence: 97%
See 4 more Smart Citations
“…The pathogenic variant c 60 + 5G > T was found in 26 patients, and brain damage was observed in two patients homozygous for this variant. This study observed that the general genotype/phenotype concordance was 83.8% when compared with identical genotypes reported in the BIOPKUdb [ 20 ].…”
Section: Reviewmentioning
confidence: 97%
“…In many cases, breast milk is used in combination with therapeutic formulas. Early initiation of treatment requires the implementation of a rapid neonatal screening programme and adequate follow-up and follow-up testing materials [ 20 ]. Sometimes, primary care providers can communicate openly with the baby's family to access the necessary specialized care.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations